Evaluasi Kinerja Aset Taman Wisata Air Cicangkang Hilir Berdasarkan Attractiveness Of Nature-Based Tourism - Hany, Siti; Suciyani, Wida Oktavia (JURNAL DESTINASI PARIWISATA, 2023)
Cicangkang Hilir Water Tourism Park is one of the tourist attractions located in West Bandung Regency. This tour has suffered damage to tourist attractions, pedestrian paths and parking areas that are not equipped with pavement, paths to attractions in weathered conditions, unmaintained shopping facilities, catering facilities, accommodation facilities, and complementary services as well as the lack of availability of hygiene and security facilities. The purpose of this study is to evaluate in more detail the performance of Cicangkang Hilir Water Tourism Park assets based on Attractiveness of Nature-Based Tourism from the dimensions of tourist attractions, accessibility, development conditions, and complementary services. The research method used is descriptive research method with qualitative and quantitative approaches. Data were collected through observation, interviews, documentation studies, and questionnaires. The results of the study indicate that the asset performance on the tourist attractions dimension is in the bad category, the accessibility dimension is in the bad category, the development conditions dimension is in the bad category, and the complementary services dimension is in the bad category so that the overall performance of Cicangkang Hilir Water Tourism Park assets has performance is not good. Keywords: Evaluation, Asset Performance, Attractions, Accessibility, Facilities